The Impact of anterior cruciate ligament rupture on athletes return to sport - A Literature review - Rusiłowicz, Rafał; Peszt, Michał Józef; Szaryński, Mikołaj; Jakubowska, Paulina; Prokopczyk, Kamila; Wasilczuk, Antoni; Poręba, Kacper; Poręba, Martyna; Matuszewska, Julia; Lewandowska-Mackiewicz, Aleksandra (Quality in Sport, 2025)
Introduction Anterior cruciate ligament (ACL) rupture is one of the most common and most burdensome injuries in sport, particularly in disciplines requiring rapid changes of direction, braking, and jumping. Despite advances in surgery and rehabilitation, return to sport (RTS) remains a complex process ~80% of athletes resume activity, yet only ~50-65% regain their preinjury level of competition. Additional challenges include a high risk of reinjury and long-term sequelae, including early degenerative changes in the knee. Psychological factors also play a key role, especially fear of reinjury and decreased trust in the operated limb. Materials and Methods This narrative review was based on original studies, meta-analyses and systematic reviews, as well as cohort, clinical, and qualitative studies concerning: the epidemiology and consequences of ACL injury outcomes of surgical and nonoperative treatment RTS rates and reinjury risk functional/psychological criteria for return to sports (RTS) decisions rehabilitation protocols and secondary prevention, and prognostic factors (age, sex, discipline, concomitant injuries) Selection of publications was guided by high clinical usefulness and direct relevance to return to sport. Summary The findings indicate that ACL reconstruction does not guarantee better RTS rates than modern nonoperative rehabilitation; the differences are clinically small. Decisions about return should not be based solely on time but on objective criteria: symmetry of strength and hop-test results, stable dynamic control, and psychological readiness. A criterion-based rehabilitation program lasting at least 9 months reduces the risk of re-injury, and neuromuscular programs reduce secondary risk by ~40-50%. The high risk of reinjury among young athletes and frequent long-term degenerative changes underscore the need for a holistic approach combining sports medicine, physiotherapy, psychological support, and long-term prevention.